Persistent and transient inefficiency: Explaining the low efficiency of Chinese big banks - Zuzana Fungáčová; Paul-Olivier Klein; Laurent Weill (Bank of Finland, Institute for Economies in Transition (BOFIT), 2018)
Considering the evidence that China's five largest state-owned banks (the Big Five) suffer from low cost efficiency, this paper decomposes overall efficiency of Chinese banks into: persistent efficiency and transient efficiency components. Low persistent efficiency reflects structural problems, while low transient efficiency is associated with short-term problems. Using the model of Kumbhakar, Lien and Hardaker (2014) based on the stochastic frontier approach, we measure persistent efficiency and transient efficiency for a large sample of 166 Chinese banks over the period 2008–2015. In line with existing evidence, we find a lower average cost efficiency of Big Five banks compared to other Chinese banks. It is almost entirely due to low persistent cost efficiency. Big Five transient efficiency is similar to other Chinese banks. Our findings support the view that major structural reforms are needed to enhance the efficiency of China's Big Five banks.
URN:NBN:fi:bof-201807241710
Keywords: C23; D24; G21; 330